Leveraging Unity for 2D Pixel Game Development: Techniques and Best Practices - Wang Ke (ITM Web of Conferences)
The rapid evolution of game development technologies emphasizes the demand for high-quality graphics and immersive gameplay. Meanwhile, there has also been a pixel art revival in the game development industry. This research explores the process of creating a 2D pixel-art adventure game with the Unity engine, figuring out some common problems that developers face and efficient solutions to them. To address these problems, the research uses several powerful toolsets offered by Unity and some other efficient approaches. This paper makes a 2D pixel-art game as a case study, focusing on the challenges of animations, map design, and gameplay mechanics. This paper found an innovative 3D-to-2D animation workflow, allowing developers to create better animations with less time. By applying Unity’s tool Tilemap Editor, this paper also found an efficient way to design levels. Additionally, this research offers some suggestions on how to improve game mechanics. The findings underscore the importance of consistent visual design and thorough playtesting. This research contributes to pixel-art games by providing practical solutions for game developers and demonstrates the potential of the Unity engine.